Ambient Air Quality Monitoring: Impetus, Complexities, Challenges and Solutions (Global Journal of Science Frontier Research, 2021)
The poor state of air quality all over the world in general, and across India in particular, is a cause for extreme concern as it is directly and indirectly linked to the deterioration of human health and economies of nations The many complexities and challenges posed by ambient air quality monitoring, prompted the World Health Organization (WHO) to suggest a road map for all nations for the year 2020 -to arrive at a consensus for effective air quality monitoring by all stakeholders -nations and governments, regulatory and controlling bodies, NGOs, scientists and researchers and private citizens.